Florence Nightingale's "greatest feat". Issue 6 (28th November 2021) - Small, Hugh
Abstract : A Nightingale family letter, dated 1857, sheds light on Florence's mathematical abilities, says Hugh Small Abstract : A Nightingale family letter, dated 1857, sheds light on Florence's mathematical abilities, says Hugh Small.